2012
DOI: 10.3109/09638288.2012.705950
|View full text |Cite
|
Sign up to set email alerts
|

Living with locked-in syndrome: an explorative study on health care situation, communication and quality of life

Abstract: most results seem to be in line with those of other studies, though larger scale and follow-up studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…People with residual LIS are probably not ideal target users either, since they can effectively and efficiently operate alternative access technologies and will thus probably find those more usable [4] or they may even prefer the (non-technological) alphabet system over an access technology. [5] Thus, the explicit recommendations of the rehabilitation professionals in our study are in line with the implicit assumption of the BCI field and the review from Tai and colleagues [1] in that BCIs are mainly interesting for people without extant physical movement, with intact cognition, and without too many concurrent problems such as spasms, cognitive impairment or seizures. Unfortunately, this conclusion is particularly bad for those people with Duchenne disease, CP or Rett syndrome who are unable to operate an access technology.…”
Section: Potential User Groupssupporting
confidence: 61%
See 1 more Smart Citation
“…People with residual LIS are probably not ideal target users either, since they can effectively and efficiently operate alternative access technologies and will thus probably find those more usable [4] or they may even prefer the (non-technological) alphabet system over an access technology. [5] Thus, the explicit recommendations of the rehabilitation professionals in our study are in line with the implicit assumption of the BCI field and the review from Tai and colleagues [1] in that BCIs are mainly interesting for people without extant physical movement, with intact cognition, and without too many concurrent problems such as spasms, cognitive impairment or seizures. Unfortunately, this conclusion is particularly bad for those people with Duchenne disease, CP or Rett syndrome who are unable to operate an access technology.…”
Section: Potential User Groupssupporting
confidence: 61%
“…[4] Snoeys and colleagues investigated the health care situation, communication, and quality of life in eight LIS patients in Belgium and found that six out of eight patients preferred the (non-technological) alphabet system to communicate and two used an infrared system. [5] Thus, while people with a total LIS definitely need a BCI to establish independent communication, [6] residual LIS patients can generally also use alternative AAC methods.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients still used alphabetic codes and eyes or body movements in their daily living, even if they had advanced technical means of communication (64%). This study corroborates the study of Snoeys et al [21] in which six out of eight studied patients using 'high-tech' AT still employed eye coded communication. Although there is a high percentage of patients in the cohort with visual impairment (66%), eye movements (alone or combined with other gestures) continue to be the most used form of non-technical communication means (50%).…”
Section: Discussionsupporting
confidence: 93%
“…However, besides the improvement of the already existing devices, brain-computer interface development is growing to enhance the available tools for communication and diagnostic purposes [23,24] and even have been already used for recreational activities such as painting in severally disabled patients [25]. A recovery of functional movements was identified in 72% of the cohort, which is in line with other studies, also showing a high percentage of improvement in chronic LIS [21,26,27], as shown in Table VI. These findings highlight the importance of rehabilitation and physical therapy.…”
Section: Discussionsupporting
confidence: 88%
“…10 Indeed, in this case, four months after suffering a basilar arter y ischaemic stroke, the patient had progressed to head nodding and shaking to communicate; a rehabilitative goal less commonly achieved. Many individuals report that they have quality of life and feel happy 8,[11][12] and it is important that healthcare professionals prioritise communication rehabilitation, rather than make assumptions about perceived quality of life. Clinicians need to be aware of changing cognitive, communicative and physical ability, with continued discussions with patients being warranted.…”
Section: Discussionmentioning
confidence: 99%